COMPARISON OF APOPTOSIS IN CONTRALATERAL RENAL TUBULAR CELLS IN ORYCTALAGUS CUNICULUS DUE TO ARTIFICIAL UNILATERAL URETERAL OBSTRUCTION, WITH AND WITHOUT VERAPAMIL - Boetoro, Djoyo M; Soetojo, Soetojo; Soebadi, Doddy M; Joewarini, Endang; P, Widodo J (Indonesian Urological Association, 2010)
Objective: To compare the effects of verapamil on the contralateral kidney affected by unilateral ureter obstruction. Material & method: The right ureter of oryctalagus cuniculus rabbits, were obstructed surgically with silk suture material, and kept alive for 14 days. One group was obstructed without other treatment, one group was given verapamil from day 7 until day 14 of the obstruction. One group was obstructed and given verapamil from day 0 through day 14. One group was given a sham operation as a control group. The contralateral kidney of all groups were harvested and processed with ApopTag. The increase of apoptotic tubular cells compared to the control group was then analyzed between each group. Results: The highest increase in apoptotic cells was in the obstructed group without verapamil, but increased significantly compared to control (p<0,001). The groups which received verapamil had lower increase of apoptotic tubular cells, in the group given verapamil for 14 days lower than the group which received verapamil only for 7 days. Both the 7 to 14 and the 0 to 14 groups were significantly lower than the group without verapamil (p=0,035 and p<0,001 respectively). Conclusion: verapamil has a protective effect on the contralateral kidney by inhibiting apoptosis caused by unilateral ureter obstruction. While the definitive treatment for urinary obstruction is to relieve it, verapamil can protect the kidney in the mean time.